Persuasive Quick-Writing about Text: Intervention for Students with Learning Disabilities. Issue 1 (January 2021) - Ciullo, Stephen; Mason, Linda H.; Judd, Laura
Researchers examined the effects of self-regulated strategy development (SRSD) to teach students with learning disabilities (LD) to compose persuasive quick-writing about text. The study included a multiple-baseline design with multiple probes for eight students with LD in grades four and five. Researchers observed a functional relationship by systematically replicating the intervention across all student participants. Following SRSD instruction for paraphrasing text and persuasive quick-writing, students increased their persuasive writing outcomes. Improvements were also noted for essay quality and writing length. Implications for future integrated writing and reading interventions are provided.